Раскройте скобки упростите выражение: 1)4-2(d+7)-2d+2*(d+3)=0 ; 2)...

0 голосов
25 просмотров

Раскройте скобки упростите выражение: 1)4-2(d+7)-2d+2*(d+3)=0 ; 2) -(7a-2*(b-4)-2)*(-4-(-3*(a-b))= (* если что это умножить)


Математика (152 баллов) | 25 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1) 4-2d-14-2d+2d+6=0
4-2d-14+6=0
-2d-10+6=0
-2d-4=0
-2d=4 /* (-1), чтобы избавиться от минуса слева
2d=-4
d=-2

(268 баллов)
0

2) -(7a-2b+8-2)*(-4*(-3a+3b))= -7a+2b-8+2*(12a-12b)= -7a+2b-8+24a-24b= 17a-22b-8

0 голосов

1)-4-2b=0
-2b=4
b=-2

(14 баллов)